The Emotional Consequences of Pro-social Behavior in Markets - Toke R. Fosgaard (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
Pro-social behavior made when buying private goods is becoming increasingly popular. Several findings from behavioral and experimental economics however emphasizes that people are less pro-social in such situations, compared to pro-social decisions in non-market contexts. This paper suggests that emotional responses are important explanations of this finding. It is first argued that the emotional response to a pro-social decision combined with private good purchase is different from the response to a similar decision in a non-market situation. Through evidence from a laboratory experiment, it is then found, that deciding on a social choice in a market exchange involves a less positive emotional reaction to others, compared to non-market situations. Moreover, subjects in market contexts are found to be less responsive to other subjects' contribution behavior, relative to the non-market contexts.
Keywords: C92; H41; M14; 330; Emotions; market exchange; pro-social behavior